Transition to Radial Approach for Neurovascular Procedures is Safe and Convenient: Characterization of a Learning Experience. Issue 5 (18th May 2020) - Vergara-Garcia, David; Gomez-Paz, Santiago; Robinson, Timothy M; Moore, Justin; Ogilvy, Christopher S; Thomas, Ajith J
Abstract: BACKGROUND: The transradial access for endovascular procedures has become a popular access point of preference for both patients and for many neuro-endovascular practitioners. OBJECTIVE: To describe a single-center experience on the transition to a radial-first approach for neurovascular procedures, focused on diagnostic angiographies, and to compare the differences in terms of length of procedure within the first 5 mo of its execution. METHODS: We performed a retrospective review of a prospective maintained cerebrovascular registry at an academic institution within the United States, to identify the expected adoption curve required to transition to a transradial route first approach focused mainly on diagnostic procedures. The 5 mo of experience were divided into 4 quartiles evenly distributed in time. The primary outcome was the total length of procedure. Secondary outcomes were access failure, radiation dose, the usefulness of ultrasound assistance and complications. RESULTS: A total of 121 transradial procedures were performed: 113 diagnostic angiographies (93%) and 8 therapeutic interventions (7%). We identified 6 access failures (5%) and 1 complication (1%). The mean length for diagnostic angiographies was 24 ± 10 min, and for therapeutic procedures was 58 ± 19 min. A multivariate regression analysis demonstrated a significant decrease in the total length of procedures after the first quartile. CONCLUSION: The transradial route shows to be a safe and convenient approach. The total length of procedure starts decreasing as providers gain experience and become more confident with this route, as seen in our 5-mo experience.